I/Ocloud: Adding an IoT Dimension to Cloud Infrastructures. - Bruneo, Dario; Distefano, Salvatore; Longo, Francesco; Merlino, Giovanni; Puliafito, Antonio (Computer (00189162), 2018)
Infrastructure as a service is a successful cloud-based utility paradigm. Its effectiveness stems from employing virtualization and enabling cloud providers to leverage elastic datacenter capabilities. To expand the reach and benefits of IaaS, the cloud must embrace the Internet of Things infrastructure as virtualized I/O resources and first-class objects at the edge.